Study to Compare and Evaluate Traditional vs. Endoscopic Septoplasty - Shrestha, I.; Pokharel, M.; Dhakal, A.; Amatya, R.C.M. (Kathmandu University Medical Journal, 2017)
Background Surgery on a deviated septum has seen several modifications since its inception starting from radical septal resection to preservation of the possible septal framework. Objective To compare the efficacies of “Endoscope Septoplasty” over “Traditional Septoplasty” in treating pathological septum and turbinates, in terms of their outcome. Method Prospective descriptive study conducted on 60 patients who presented to the Department of ENT, Kathmandu University School of Medical sciences during a period of two years. The severity of the symptoms of the patients was scored using a visual analogue scale which was compared post operatively to subjectively evaluate the efficacy of either surgery. Objective assessment was done by nasal endoscopy. P value in case of subjective and objective evaluation was done by applying Z- test. Result The mean age ± SD was 29.5±1.2 .Maximum patients fell into age group of 21-30 with 31.7 % followed by 11-20 with 28.3% and then 31-40 with 25 %. There were total 35 males (58.3%) and 25 females (41.7%). Among the symptoms, nasal obstruction seems to be dominating with total of 83.3%, followed by postnasal drip with 66.6% and then headache with 60%. The types of dislocation was compared, there were 66.7% cases with DNS and Spur whereas only 10 % with isolated spur. C shaped deformity was seen in 30% and S shaped in 26.6 % cases. Significance in Z test, is seen in subjective assessment post surgery for nasal obstruction, headache and rhinorrhea and for objective assessment post surgery for persistent contact with turbinates. (p value set to 0.01) Conclusion Endoscopic surgery is an evolutionary step towards solving the problems related to deviated nasal septum. It is safe, effective and conservative alternative to conventional septal surgery.